Extraction of antioxidant compounds in watermelon and cantaloupe from Comarca Lagunera - Ramírez-Aragón, Mercedes Georgina; Borroel-García, Victoria Jared; López-Martínez, José Dimas; Nieto-Garibay, Alejandra; García-Hernández, José Luis (Ecosistemas y Recursos Agropecuarios, 2024)
Watermelon and cantaloupe are fundamental vegetables. The objective was to study its antioxidant properties in different parts of the fruits and identify the best extraction method to obtain active compounds. The quantification of total phenolic compounds (TPC), total flavonoids (TFC), and total antioxidant activity by ABTS and DPPH was analyzed using spectrophotometric techniques. The contents of TPC were reported as 4.4 and 48.1 mg GAE g-1 for watermelon peel and cantaloupe pulp, respectively. The TFC was 157 and 213 mg QE g-1 for watermelon and cantaloupe seeds. The ABTS technique ranged from 26147.6 for cantaloupe pulp to 9302.3 μM Trolox g-1 for watermelon peel, while the DPPH technique showed the highest antioxidant activity in cantaloupe pulp with a value of 18989.5 μM Trolox g-1. The most efficient extraction method was with samples subjected to heat, highlighting the extraction of watermelon seeds due to their high antioxidant content.